2016
DOI: 10.1007/s10995-016-2158-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Nicotine Exposure on Infant Language Development: A Cohort Follow Up Study

Abstract: Objectives To study the longitudinal effects of prenatal nicotine exposure on cognitive development, taking into consideration prenatal and postnatal second-hand smoke exposure. Methods A cohort follow up study was carried out. One hundred and fifty-eight pregnant women and their infants were followed during pregnancy and infant development (at 6, 12, 30 months). In each trimester of pregnancy and during postnatal follow-up, a survey was administered to obtain sociodemographic data and the details of maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 30 publications
5
34
0
Order By: Relevance
“…Consistent with earlier studies, our data provide evidence to support the argument that prenatal exposure to ETS is negatively correlated with children’s cognitive development [10,25,26,27,28,30]. Our study also reached the same conclusion as earlier studies that children’s language abilities were related to prenatal exposure to ETS [10,25,27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with earlier studies, our data provide evidence to support the argument that prenatal exposure to ETS is negatively correlated with children’s cognitive development [10,25,26,27,28,30]. Our study also reached the same conclusion as earlier studies that children’s language abilities were related to prenatal exposure to ETS [10,25,27].…”
Section: Discussionsupporting
confidence: 92%
“…While the impact of active maternal smoking on child development is well established, the association between prenatal ETS exposure and child development remains mixed [21]. Some studies show that prenatal exposure to ETS has been associated with negative childhood psychosocial development, such as in learning and memory [22]; delinquent, aggressive, and externalizing behaviors [23]; poor preschool temperament and erratic emotionality [24]; negative cognitive, language, fine-motor, and social–emotion development [25,26,27]; and low mental development index scores [28,29]. Other research has found no association after adjusting for the mother’s age, educational attainment, and annual family income.…”
Section: Introductionmentioning
confidence: 99%
“…14 There is a growing body of evidence that has assessed the neurobehavioural consequences of prenatal cigarette exposure on infant development during the first year of life. 15,16 Although reviews have been carried out assessing prenatal exposure on developmental outcomes, 17,18 the current review is the first meta-analysis assessing neurobehavioural outcomes within the first year of life.…”
mentioning
confidence: 99%
“…The aim was to investigate the effect of prenatal, perinatal, and postnatal clinical and psychosocial factors on infant morning cortisol levels at 12 months of age in the same cohort. Thus, from the prenatal period, we have taken into account variables related to the mother's cortisol levels that may alter infant behaviour (maternal tobacco use, life events, anxiety, and emotional stability; Hernández‐Martínez et al, ; Hernández‐Martínez, Arija, Balaguer, Cavallé, & Canals, ). We have also adjusted the analyses by using factors from the perinatal period (mode of delivery, gestational age, infant birth weight, and parity) that can affect the functioning of the HPA from an early stage (Marceau et al, ).…”
Section: Discussionmentioning
confidence: 99%